KESADARAN HUKUM MASYARAKAT TERHADAP PELANGGARAN LALU LINTAS DI DESA TENGKET KECAMATAN AROSBAYA KABUPATEN BANGKALAN - Arafat, Nabila; Imam Faisal, Bagus; Ernawati; Sunardjo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the legal awareness of the community towards traffic violations in Tengket Village, Arosbaya District, Bangkalan Regency. The method used is descriptive qualitative, with data collection through observation, interviews, and documentation. The research results indicate that the level of legal awareness in the community is still low, as evidenced by numerous violations such as not wearing helmets and ignoring traffic signs. Additionally, factors such as poor road conditions, lack of lighting, and insufficient socialization regarding traffic regulations contribute to this issue. The community also perceives violations as trivial, reflecting a mindset that needs to be changed. This research is expected to contribute to efforts to enhance legal awareness and traffic safety in Tengket Village.